PERANCANGAN TATA LETAK PENYIMPANAN BAJU DI GUDANG BEHERO - Supriono, Supriono; Sumantika, Arsyad (Computer Science and Industrial Engineering, 2023)
One of the strategic operational choices that affects the long-term efficacy of the business's operations is layout. Finding the ideal balance between space expenses and material handling costs is the goal of warehouse planning. The class-based dedicated storage strategy is used in this study, which classifies products into three, four, or five categories depending on how frequently they are picked up. The suggested clothes layout adheres to the Class Based Storage approach, in which clothing is arranged according to popularity, similarity, size, and other factors.Fast moving products are stored on the first and second shelves, which are located in the front. The shelf has three levels, with the middle level being used for S and M sizes because they are the most popular and are therefore easier for staff to access. Because the bottom shelf is simpler to reach than the top shelf and can be picked up by employees without the use of tools, size L and XL have an average sales level there. Jumbo size products (XXL, XXXL, and XXXXL) are positioned on the third (top) shelf since they have the lowest sales rates.